2020
DOI: 10.1557/mrc.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxy growth of nonmagnetic Weyl semimetal LaAlGe thin film

Abstract: Here, the authors report a detailed method of growing LaAlGe, a nonmagnetic Weyl semimetal, thin film on silicon(100) substrates by molecular beam epitaxy and their structural and electrical characterizations. About 50-nm-thick LaAlGe films were deposited and annealed for 16 h in situ at a temperature of 793 K. As-grown high-quality films showed uniform surface topography and near ideal stoichiometry with a body-centered tetragonal crystal structure. Temperature-dependent longitudinal resistivity can be unders… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…H is the slope of ρ xy [Fig.1(d,e)]. Carrier concentration shows reduction above 40 K and is consistent with result obtained in thin films 30. This is coincident with increased resistivity [Fig.1(b)] above 40 K, indicating that ρ(T ) is also influenced by changes in n, in addition to phonon-related scattering induced by increased…”
supporting
confidence: 86%
See 1 more Smart Citation
“…H is the slope of ρ xy [Fig.1(d,e)]. Carrier concentration shows reduction above 40 K and is consistent with result obtained in thin films 30. This is coincident with increased resistivity [Fig.1(b)] above 40 K, indicating that ρ(T ) is also influenced by changes in n, in addition to phonon-related scattering induced by increased…”
supporting
confidence: 86%
“…[23][24][25][26] LaAlGe features type-II Weyl nodes. [27][28][29] Thin films of LaAlGe show metallic resistivity, small residual resistivity ratio RRR = ρ(300 K)/ρ (5 K) = 1.17, relatively high residual resistivity of about 87 µΩ cm, single band electronic transport and 7×10 21 cm −2 carrier concentration at 5 K. 30 In particular, contribution of Weyl points at the Fermi surface, dimensionality and characteristics of such states are important. Here we perform quantum oscillation studies of LaAlGe.…”
mentioning
confidence: 99%
“…[9,12] Hall resistivity, ρ xy , measurements were taken at various temperatures starting from room temperature (300 K) down to 5 K and in a magnetic field up to AE4 T. Studies have shown that taking Hall measurements in positive as well as negative field directions helps to improve the precision of data. [18] Separate devices of 30 and 50 nm thick FeSn grown on different substrates were used for the Hall measurements. Figure 8 displays the ρ xy measured for the 30 nm thick FeSn device on Si(100).…”
Section: Resultsmentioning
confidence: 99%
“…Materials grown by conventional epitaxy include Cd 3 As 2 , NbP, TaP, Na 3 Bi, Sr 3 PbO, LaAlGe, Co 3 Sn 2 S 2 , and TaIrTe 4 . [83][84][85][86][87][88][89][90][91] In most of these cases, the more volatile element (i.e., As, P, S, Te) is held in excess, while the less volatile element controls the growth rate. However, in the cases of materials like LaAlGe or Na 3 Bi, more careful flux matching is needed.…”
Section: Molecular Beam Epitaxy Growth Of Topologically Nontrivial Thin Filmsmentioning
confidence: 99%